PENERAPAN LOGIKA FUZZY UNTUK MEMPREDIKSI CUACA HARIAN DI BANJARBARU - Uli Mahanani; Arfan Eko Fahrudin; Nurlina Nurlina (Jurnal Fisika FLUX, 2015)
Information about the weather is very important because the weather is one of the factors to support the smooth operation and human activities. Along with the development of science and technology, the weather can be predicted by methods based expertise. One method based expertise that can be used to predict the weather is fuzzy logic. Fuzzy logic is a system built by definition, ways of working and a clear description. This study provides a review of daily weather prediction in Banjarbaru using input data of maximum air temperature, air humidity average daily, 24 hours a pressure difference, and product Numerical Weather Prediction (NWP) humidity above a layer of 850 mb, 700 mb and 500 mb. The prediction model is determined by the type of fuzzy logic method Mamdani which will produce output in the form of weather predictionweather conditions in Banjarbaru by category sunny, cloudy, slight rain, moderate rain, and heavy rain. The verification results January 2013 until September 2014 showed the smallest verification value is 56.5% and the value of the largest verification is 88.3%. On average verification in January 2013 to September 2014 was 70.1%. Verification results obtained show that the predicted results with fuzzy logic in this study can be declared fit for use as a daily weather prediction models in Banjarbaru.